SUSTAINABLE STARTUPS: THE GAME CHANGING ROLE OF ENTERPRISE RESOURCE PLANNING - Winasis, Shinta; A A B Dinariyana (FEB Universitas Sam Ratulangi Manado, 2024)
In the rapidly evolving landscape of Industry 4.0, startup companies are fostering innovation, attracting investment, and creating job opportunities, thus pivotal to economic growth. Despite their potential, the success rate of Indonesian startups achieving unicorn or decacorn status remains low. Many Indonesian startups face significant challenges such as limited access to funding, market competition, and operational inefficiencies, leading to high rates of closure and bankruptcy. Addressing these issues is crucial, to ensure that Indonesian startups in achieving significant growth and investment success, innovative solutions are essential. This study explores the implementation of Enterprise Resource Planning (ERP) systems as a strategic approach to enhance the sustainability and competitive edge of startups. Through a systematic literature review, founder/manager interviews and expert interviews, the research identifies ERP as a crucial tool for integrating business processes, improving operational efficiency, and enabling data-driven decision-making. While ERP alone does not guarantee startup success, it offers significant advantages by providing real-time insights into company operations, which are vital for strategic planning and investor confidence. The findings serve as a guide for startups aiming to implement ERP systems to support their business continuity and growth. Keywords: Startup Companies; Enterprise Resource Planning; Sustainability; Innovation; Industry 4.0